2009
DOI: 10.1055/s-0029-1237118
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Sleep

Abstract: The neurobiology of sleep and narcolepsy is reviewed. Non-rapid eye movement (NREM) sleep is generated by neurons in the preoptic region of the hypothalamus and adjacent basal forebrain. Lesions in these regions cause insomnia. Stimulation of these regions rapidly produces sleep onset. The key brain structure for generating REM sleep is the pons and adjacent portions of the midbrain. Damage to the pons and/or caudal midbrain can cause abnormalities in REM sleep. The persistent sleepiness of narcolepsy is a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 148 publications
(189 reference statements)
0
55
1
4
Order By: Relevance
“…Based on studies of unihemispheric sleep in marine mammals, it is widely appreciated that the minimal unit for sleep expression may not encompass the entire brain [59]. However, defining which parts of the brain engage in sleep expression is a challenge.…”
Section: Local Sleepmentioning
confidence: 99%
“…Based on studies of unihemispheric sleep in marine mammals, it is widely appreciated that the minimal unit for sleep expression may not encompass the entire brain [59]. However, defining which parts of the brain engage in sleep expression is a challenge.…”
Section: Local Sleepmentioning
confidence: 99%
“…The firing rate of cortical neurons has generally been reported to be reduced during NREM relative to wakefulness and REM (5,6). A few studies have reported cortical neurons with the opposite pattern.…”
mentioning
confidence: 99%
“…Multiple monoamines, including dopamine (DA), serotonin, norepinephrine, and histamine, as well as acetylcholine and the neuropeptide, hypocretin [ 28 ] , appear to be involved in the modulation of the sleep-wake cycle. Serotonin and DA both function to promote waking and to inhibit slowwave sleep and/or rapid eye movement sleep [ 29 ] .…”
Section: Sleep Physiologymentioning
confidence: 99%